Extent of misuse and dependence of codeine-containing products among medical and pharmacy students in a Nigerian University (2019)
Background: Misuse and dependency of opioids especially codeine-containing products is of increasing global concern. Inappropriate use of opioids among healthcare students could affect quality of service and ethical conducts of these future professionals, thereby putting the society at risk. This study aimed to evaluate knowledge and perception of medical and pharmacy students in a Nigerian tertiary University on use of opioids with focus on codeine-containing products. Methods: A cross-sectional survey among 335-medical and 185-pharmacy students from University of Ibadan, Nigeria, between September and December 2018, using a self-administered semi-structured questionnaire. Results: A total of 178 (34.2%) in multiple responses had used opioid-containing products among the respondents, of this, 171 (96.1%) used codeine-containing formulation. Precisely, 146 (28.1%) of the students had used codeine-containing products before, of this, 16 (11.0%) used the products for non-medical or recreational purpose regarded as a misuse/ abuse. In all, 201 (38.7%) had good knowledge of opioid use, with 51 (34.9%) among those who had used opioids and 150 (40.1%) among those who had not used opioids (X2 = 1.186; p = 0.276). Majority (469; 90.2%) had good perception of risks associated with opioid use; comprising (130; 89.0%) among those who had taken opioids and (339; 90.6%) among those who had not taken opioids before (X2 = 0.304; p = 0.508). Logistic-regression shows that students who experienced some side effects to be experienced again 22.1 [AOR = 22.1, 95% CI: (5.98–81.72)] as well as those pressured into using codeine-containing products 10.6 [AOR = 10.6, 95% CI: (1.36–82.39)] had more tendency of misuse. Conclusion: There is a potential for misuse of codeine-containing products among medical and pharmacy students. Peer-influence and experience of some side effects are possible predictors of misuse among the students. Thus, healthcare students’ curriculum should incorporate preventive programme, while public education and policy that favours peer-support programme on medication misuse is advocated for healthcare students.